2010
DOI: 10.1088/0266-5611/26/8/085003
|View full text |Cite
|
Sign up to set email alerts
|

A two-component μ-Hunter–Saxton equation

Abstract: In this paper, we propose a two-component generalization of the generalized Hunter-Saxton equation obtained in [22]. We will show that this equation is a bihamiltonian Euler equation, and also can be viewed as a bivariational equation.2000 Mathematics Subject Classification. 37K10, 35Q51.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
0
37
0
2
Order By: Relevance
“…It was shown that the system describes the geodesic flows on semidirect product Lie group of diffeomorphism group D s .S/ and the space of scalar functions on S [17,18]. One can readily verify that it also describes pseudo-spherical surfaces [19], namely there exist forms associated with the system…”
Section: Y Zhangmentioning
confidence: 94%
See 1 more Smart Citation
“…It was shown that the system describes the geodesic flows on semidirect product Lie group of diffeomorphism group D s .S/ and the space of scalar functions on S [17,18]. One can readily verify that it also describes pseudo-spherical surfaces [19], namely there exist forms associated with the system…”
Section: Y Zhangmentioning
confidence: 94%
“…System can be viewed as a mid‐way one between the two‐component Camassa–Holm system and two‐component Hunter–Saxton system, which admits the Lax‐pair alignedrightφxxleft=λm+λ2ρ2φ,rightrightφtleft=12λuφx+12uxφ. It was shown that the system describes the geodesic flows on semidirect product Lie group of diffeomorphism group scriptDs(double-struckS) and the space of scalar functions on double-struckS . One can readily verify that it also describes pseudo‐spherical surfaces , namely there exist forms associated with the system alignedrightω1left=14λ2MathClass-open(ρ21MathClass-close)+12λm+1dx+14λ2uMathClass-open(1ρ2MathClass-close)14λ1+2umρ2+2ux+12μudt,rightrightω2left=…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the KdV equation could be regarded as Euler equations on the dual of Virasoro algebra vir with different inner products ( [7,9,11,12]). Let us remark that V.I.Arnold in [1] suggested a general framework for the Euler equation on an arbitrary Lie group G, which is useful to characterize a variety of conservative dynamical systems, please see e.g., [2,6,7,8,9,11,12,15,17,18] and references therein. If the corresponding Lie algebra is G, then the Euler equation (1.1) on G * could describe a geodesic flow w.r.t a suitable one-side invariant Riemannian metric on Lie group G.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we consider the Cauchy problem of the following two‐component periodic μ ‐Hunter–Saxton system {μ(u)(t)utxx=2μ(u)ux2uxuxxuuxxx+ρρxγ1uxxx,t>0,xR,ρt=(ρu)x2γ2ρx,t>0,xR,u(0,x)=u0(x),ρ(0,x)=ρ0(x),xR,u(t,x+1)=u(t,x),ρ(t,x+1)=ρ(t,x),t0,xR, where μ(u)=double-struckSunormaldx, double-struckS=double-struckR/double-struckZ and γidouble-struckR, i = 1,2. The system was introduced by Zou . By integrating both sides of the first equation in the system over the circle double-struckS and using the periodicity of u , one obtains μ(ut)=μ(u)t=0,…”
Section: Introductionmentioning
confidence: 99%
“…By integrating both sides of the first equation in the system over the circle double-struckS and using the periodicity of u , one obtains μ(ut)=μ(u)t=0, which implies the following two‐component periodic μ ‐Hunter–Saxton system {utxx=2μ(u)ux2uxuxxuuxxx+ρρxγ1uxxx,t>0,xR,ρt=(ρu)x2γ2ρx,t>0,xR,u(0,x)=u0(x),ρ(0,x)=ρ0(x),xR,u(t,x+1)=u(t,x),ρ(t,x+1)=ρ(t,x),t0,xR. This system is a two‐component generalization of the generalized Hunter–Saxton equation obtained in . Zou shows that this system is both a bi‐Hamiltonian Euler equation and a bi‐variational equation. Liu and Yin established the local well‐posedness, precise blow‐up scenario and global existence result to the system .…”
Section: Introductionmentioning
confidence: 99%